Murphy's slaw - Logan, Elizabeth, 1937- (Logan, Elizabeth, 1937- Alaskan diner mystery., 2021)
"Charlie Cook must investigate the disappearance of a local farmer, known for growing giant cabbages, in this charming and enthralling new entry in the Alaskan Diner Mysteries"--